If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(x + 7) = 3(x + 4) Reorder the terms: 14(7 + x) = 3(x + 4) (7 * 14 + x * 14) = 3(x + 4) (98 + 14x) = 3(x + 4) Reorder the terms: 98 + 14x = 3(4 + x) 98 + 14x = (4 * 3 + x * 3) 98 + 14x = (12 + 3x) Solving 98 + 14x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 98 + 14x + -3x = 12 + 3x + -3x Combine like terms: 14x + -3x = 11x 98 + 11x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 98 + 11x = 12 + 0 98 + 11x = 12 Add '-98' to each side of the equation. 98 + -98 + 11x = 12 + -98 Combine like terms: 98 + -98 = 0 0 + 11x = 12 + -98 11x = 12 + -98 Combine like terms: 12 + -98 = -86 11x = -86 Divide each side by '11'. x = -7.818181818 Simplifying x = -7.818181818
| z+12=2(4z-7) | | 6+4(3-4x)=-2(1+3x) | | 15/3=x/5 | | 2(-2x-5)+4x=10 | | -5(5y-5)+2(2y+5)= | | (2x+5y)+(x+y)=1 | | z+12=4z-7 | | 90+90+(2x-4)+(3x-29)=360 | | 45x-9y=18 | | -9=3x+5 | | 4x^2+45=20x | | 848/0 | | w(w-6)=0 | | 8t+2(1-5t)= | | 4x^2+28x=-61 | | -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 | | 2/5=x/25 | | 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) | | -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 |